Expectations and the Cross-Section of Stock Returns. - La Porta, Rafael (Journal of Finance, 1996)
Previous research has shown that stocks with low prices relative to book value, cash flow, earnings, or dividends (that is, value stocks) earn high returns. Value stocks may earn high returns because they are more risky. Alternatively, systematic errors in expectations may explain the high returns earned by value stocks. The author tests for the existence of systematic errors using survey data on forecasts by stock market analysts. He shows that investment strategies that seek to exploit errors in analysts' forecasts earn superior returns because expectations about future growth in earnings are too extreme.